Kinetics of Evaporation - Gerasimov, Denis N. (Springer Series in Surface Sciences,, 2018)
This monograph discusses the essential principles of the evaporation process by looking at it at the molecular and atomic level. In the first part methods of statistical physics, physical kinetics and numerical modeling are outlined including the Maxwell's distribution function, the Boltzmann kinetic equation, the Vlasov approach, and the CUDA technique. The distribution functions of evaporating particles are then defined. Experimental results on the evaporation coefficient and the temperature jump on the evaporation surface are critically reviewed and compared to the theory and numerical results presented in previous chapters. The book ends with a chapter devoted to evaporation in different processes, such as boiling and cavitation. This monograph addresses graduate students and researchers working on phase transitions and related fields.